Estresse, ansiedade e qualidade de vida em professores: efeitos do relaxamento progressivo - Freitas, Geisa Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Studies with public shocol teachers report symptoms of stress, anxiety and low life quality of these professionals, but few had intervention proposals. From this gap, the aim of this study was to investigate the effects of Jacobson's Progressive Relaxation adapted by Sandor in stress measures, anxiety and Quality of Life of public school teachers. This study smaple comprised 105 teachers from Brazil's public schools in their teaching activities. Exclusion criteria were: presence of pyschiatric diagnoses, pregnancy, being in removal of the activities as a teacher, or have less than one year working in this function. The sample was divided into three groups: intervention (G1), lecture (G2) and passage of time (G3). To stress measures, we used the ISSL and the EVENT; Quality of Life was measured using the instrumetn proposed by the World Helth Organizations. WHOQOL-bref, to measure anxiety, we used the Beck Anxiety Inventory (BAI). The data were summarized quantitatively by means of the functions of descriptive statistics; ANOVA was used for inferential analysis and comparison of more than two means. Significant improvement was found (p=0.004) in the post-test for stress measurement with ISSL. There have improvements in the perception of job stress and anxiety in the post-test for the G1, not statistically significant, however, clearly indicating a trend towards improvement compared the results with G2 and G3. The measure of quality of life in the sample were consistent with those described in the literature and the valuation difference between the three groups in the pre and post-test was not statistically significant. It is, therefore, there was a significant change in stress symptoms presented to the participants and the G1, the measures of anxiety and vulnerability of the participants before occupational stressors has been identified trend to improvement compared with the results of G2 and G3. It was found that comparing pre and...

Estudos com professores de escolas públicas indicam sintomas de estresse, de ansiedade e baixa qualidade de vida destes profissionais, porém, poucos apresentaram propostas de intervenção. A partir desta lacuna, o objetivo deste estudo foi investigar os efeitos do Relaxamento Progressivo de Jabobson adaptado por Sandor nas medidas de estresse, ansiedade e qualidade de vida de professores de escolas públicas. Constituíram a amostra 105 professores de escolas públicas estaduais no desempenho de suas atividades de docência. Foram critérios de exclusão: presença de diagnóstico psiquiátricos, gravidez, estar em afastamento das atividades laborais como professor, ter tempo de função inferior a um ano. A amostra foi dividida em três grupos: intervenção (G1), palestra (G2) e passagem do tempo (G3). Para medidas da estresse, foram utilizados o ISSL e a EVENT; a qualidade de vida foi mensurada por meio do instrumento proposto pela Organização Mundial da Saúde: WHOQOL abreviado; para medida de ansiedade, utilizou-se o Inventário de Ansiedade Beck (BAI). As informações coletadas foram sintetizadas, quantitativamente, por meio das funções da estatística descritiva; utilizou-se teste ANOVA para análise interferencial e comparação entre mais de duas médias. Foi identificada melhora significativamente (p= 0,004) no pós-teste para medida de estresse com o ISSL. Verificaram-se melhoras na percepção do estresse no trabalho e na ansiedade no pós-teste para o G1, sem significância estatística, porém, claramente indicando uma tendência à melhora quando comparados os resultados com G2 e G3. A medida de qualidade de vida encontrada na amostra foi condinzente com o descrito na literatura e a diferença de avaliação entre os três grupos no pré e pós teste não foi estatisticamente significativa. Verificou-se, portante, ter havido alteração significativa nos sintomas de estresse apresentados para os participantes do G1 e, nas...
Keywords: Stress (Fisiologia); Ansiedade; Qualidade de vida; Relaxantes musculares; Stress (Physiology)